Audiovisual multisensory integration - Spence, C (2007)
Over the last 50 years or so, a large body of empirical research has demonstrated the importance of a variety of low-level spatiotemporal factors in the multisensory integration of auditory and visual stimuli (as, for example, indexed by research on the ventriloquism effect). Here, the evidence highlighting the contribution of both spatial and temporal factors to multisensory integration is briefly reviewed. The role played by the temporal correlation between auditory and visual signals, stimulus motion, intramodal versus crossmodal perceptual grouping, semantic congruency, and the unity assumption in modulating multisensory integration is also discussed. Taken together, the evidence now supports the view that a number of different factors, both structural and cognitive, conjointly contribute to the multisensory integration (or binding) of auditory and visual information. © 2007 The Acoustical Society of Japan.